MENINJAU KEMBALI EKONOMIKA NEOKLASIK - Mubyarto, Mubyarto (Journal of Indonesian Economy and Business, 2002)
Economic Faculties in Indonesian Universities have been teaching economics in the Neoclassical tradition as in Samuelsonâs Economics, a combination of Classical liberalism and Marginal Utility theory. But the development experience in the last 32 years which have created extreme inequalities in the distribution of wealth and income have raised the issues of economic and social justice. âSocial economics insist that justice is a basic element of social economic organization â (which is) far more important than allocative efficiency. Inefficient societies abound and endure in the historical record but societies that lack widespread conviction as to their justness are inherently unstable. â â¦.. The most fundamental difference between the social-economics perspective and that of mainstream economics is that the latter has for its principal focus the production of good and services while the former focuses on the reproduction of society. (E.K. Hunt, History of Economic Thought A Critical Perspective, 1979). An atmosphere need to be created whereby economists are prepared to take on what is best from the social science; economics is more likely to be changed by its friends than by its critics; in business as well as in theory we prefer not the metaphor of the invisible hand but rather that of the âinvisible handshakeâ the spirit of cooperation and competition. 1)Keywords: justice, ideology, Neoclassical Economics, and social economics